Terapi Relaksasi Benson untuk Manajemen Nyeri Pasca Sectio Caesarea - Nabilah Firgy Nisa; Lily Wahyuni Romadhon; Citra Setyo Dwi Andini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Pain is one of the most common complaints experienced by post-cesarean section patients due to surgical incisions. Uncontrolled pain may hinder early mobilization, reduce comfort, and delay the recovery process. Benson Relaxation Therapy is a non-pharmacological intervention that can be used to help reduce pain intensity. This study aimed to analyze the implementation of Benson Relaxation Therapy in pain management among post-cesarean section patients. The study employed a descriptive design with a pre-test and post-test approach involving five post-cesarean section patients experiencing acute pain. Data were collected through interviews, observations, physical examinations, documentation, and pain assessment using the Numeric Rating Scale (NRS). Benson Relaxation Therapy was administered for 10–15 minutes daily over three consecutive days. The results showed that all patients experienced a gradual reduction in pain intensity following the intervention. Initial pain scores ranged from 5 to 8 and decreased to 1–2 by the third day. In addition, patients appeared more relaxed, comfortable, and demonstrated improved mobility. Benson Relaxation Therapy can be applied as a safe, simple, and effective non-pharmacological intervention to help reduce pain intensity in post-cesarean section patients.